Study of Dissimilar Welding AA6061 Aluminium Alloy and AZ31B Magnesium Alloy with ER5356 Filler Using Friction Stir Welding - M. I. I., Mahamud; M., Ishak; Aiman, Mohd Halil (IOP Publishing Ltd, 2017)
This paper is to study of dissimilar welding AA6061 aluminium alloy and AZ31B magnesium alloy with ER5356 filler using friction stir welding. 2 mm thick plates of aluminium and magnesium were used. Friction stir welding operations were performed at different rotation and travel speeds and used the fixed tilt angle which is 3°. The rotation speeds varied from 800 to 1100 rpm, and the travel speed varied from 80 to 100 mm/min. In the range rotation speed of 800 to 1000 rpm and welding speed of 80 to 100 mm/min there are no defect at the weld. Tensile test show the higher tensile strength is 198 MPa and the welding efficiency is about 76%.